Catalysis of alkene epoxidation by manganese(II) and (III) complexes of both Schiff base and reduced Schiff base ligands utilizing environmentally benign H2O2. (1st April 2018) - Egekenze, Rita; Gultneh, Yilma; Butcher, Ray
Graphical abstract: Mn(III) and Mn(II) complexes of Schiff base and reduced Schiff ligands were used as catalysts in the epoxidation of olefins with H2 O2 in the presence of ammonium acetate/acetic acid or triethylamine/perchloric acid systems as cocatalyst/buffer in a mixture of 1:1:2 of CH2 Cl2 /CH3 OH/CH3 COCH3 solvent at room temperature and 0 °C. The complexes of the reduced Schiff base ligands gave higher epoxide yields than the complexes of Schiff base ligands at both room temperature and 0 °C. The ammonium acetate/acetic acid system gave a slightly higher epoxide yield than the triethylamine/perchloric acid system. Epoxide yields were based on steric effect of the catalyst, flexibility of the ligand, temperature and cocatalyst. Abstract: Mono and disubstituted tridentate Schiff base ligands were synthesized from the reaction of 2(2-aminoethyl)pyridine with 5-bromosalicylaldehyde (H-L 1 ) and 3, 5-dibromosalicylaldehyde (H-L 2 ) respectively, which were subsequently reacted with NaBH4 to yield the corresponding reduced Schiff base ligands H-rL 1 and H-rL 2 . The complexes; Mn III -(L 1 )2 (1), Mn III -(rL 1 )2 (3), and Mn II -(L 2 )2 (2), Mn II -(rL 2 )2 (4) were obtained by the reaction of the ligands with Mn(ClO4 )2 ·6H2 O. The ligands and complexes were characterized by UV–Vis, ESI-MS and FT-IR spectroscopy. The 1 H NMR spectra of the ligands as well as the crystal structures, and electrochemical properties of the complexes were obtained. The crystal structures of Mn III -(L 1 )2 and Mn II -(L 2 )2 show coordination of the ligands in tridentate mode in octahedral geometry. Cyclic voltammetric studies of Mn-(L 1 )2 and Mn-(L 2 )2 in acetonitrile solution show two prominent reversible peaks attributed to the redox processes: Mn(II)/Mn(III), ( E 1/2 = 0.203–(−0.204 V) and Mn(III)/Mn(IV), ( E 1/2 = 1.103–0.195 V) versus Ag/AgCl while that of Mn-(rL 4 )2 showed three quasi reversible peaks suggesting three redox couples: Mn(II)/Mn(III) ( E 1/2 = −0.109); Mn(III)/Mn(IV), ( E 1/2 = 0.125 and (Mn(IV)/Mn(V), ( E 1/2 = 0.649) vs Ag/AgCl. Epoxidation of cyclohexene and 1-hexene by hydrogen peroxide catalyzed by the manganese complexes gave epoxide yield of 42–53% with a turnover of 10.50–13.25 after 20 h of reaction for the reduced Schiff base complexes Mn III -(rL 1 )2 and Mn II -(rL 2 )2 at 0 °C.